School Feeding and Nutritional Status of Students in Dubti District, Afar, Northeast Ethiopia: Comparative Cross-Sectional Study - Hussein K; Mekonnen TC; Hussien FM; Alene TD; Abebe MS (Dove Medical Press, 2023)
Kedir Hussein,1 Tefera Chanie Mekonnen,1 Foziya Mohammed Hussien,1 Tilahun Dessie Alene,2 Melese Shenkut Abebe3 1School of Public Health, College of Medicine and Health Science, Wollo University, Dessie, Ethiopia; 2Department of Pediatrics, School of Medicine, College of Medicine and Health Science, Wollo University, Dessie, Ethiopia; 3Department of Anatomy, School of Medicine, College of Medicine and Health Science, Wollo University, Dessie, EthiopiaCorrespondence: Melese Shenkut Abebe, Department of Anatomy, School of Medicine, College of Medicine and Health Science, Wollo University, Dessie, Ethiopia, Email melese19@yahoo.comBackground: Providing food to the school children is an important means of compacting malnutrition especially in high food insecure areas. Our study was conducted to evaluate the association between school feeding and nutritional status among students in primary schools of Dubti district in Afar region.Methods: A comparative cross-sectional study was employed on 936 primary school students from March 15- 31/2021. For data collection, structured questionnaire was administered by the interviewer. Descriptive statistics as well as logistic regression was conducted. WHO Anthro-plus software was used to compute anthropometric data. Adjusted odds ratio with 95% CI was calculated to identify the level of association. Variables with p-value < 0.05 were taken as statistical level of significance.Results: A total of 936 primary school students, with 100% response rate, were included in the current study. The prevalence of stunting in school fed and non-school fed students was 13.7% 95% CI (11, 17) and 21.6% 95% CI (18, 25), respectively. The prevalence of thinness in school fed and non-school fed students was 4.9% 95% CI (3, 7) and 13.9% 95% CI (11, 17), respectively. Even though no record of overweight and obesity were found in non-school fed students, 5.4% 95% CI (3, 7) among school fed students was overweight/obese. Grade level, diet information source, media source availability, maternal age, the critical time for hand washing, and nutrition education were found to be predictors of malnutrition in both groups of students.Conclusion: The magnitude of stunting and thinness in school fed students is found to be lower, but overnutrition is higher than non-school fed. Grade level of students and diet selection information were determinants that affected the nutritional status of students. Coordinated education regarding good feeding practice, and personal as well as environmental hygiene should be given to the students and their families.Keywords: school feeding, nutritional status, students, malnutrition